Strategic management of product development - Wong, Soon Yee. (2009)
The study of new product success and failure has been a focus of academic researchers for several years. A 1993 study of product development performance measures identified 61 research projects concerned with discovering the factors leading to product development success. However, these studies use different measures and cover a variety of industries and market situations[12].